Sendai Virus Induces Persistent Olfactory Dysfunction in a Murine Model of PVOD via Effects on Apoptosis, Cell Proliferation, and Response to Odorants. - Jun Tian (PLoS ONE, 2016)
Viral infection is a common cause of olfactory dysfunction. The complexities of studying post-viral olfactory loss in humans have impaired further progress in understanding the underlying mechanism. Recently, evidence from clinical studies has implicated Parainfluenza virus 3 as a causal agent. An animal model of post viral olfactory disorders (PVOD) would allow better understanding of disease pathogenesis and represent a major advance in the field.To develop a mouse model of PVOD by evaluating the effects of Sendai virus (SeV), the murine counterpart of Parainfluenza virus, on olfactory function and regenerative ability of the olfactory epithelium.C57BL/6 mice (6-8 months old) were inoculated intranasally with SeV or ultraviolet (UV)-inactivated virus (UV-SeV). On days 3, 10, 15, 30 and 60 post-infection, olfactory epithelium was harvested and analyzed by histopathology and immunohistochemical detection of S-phase nuclei. We also measured apoptosis by TUNEL assay and viral load by real-time PCR. The buried food test (BFT) was used to measure olfactory function of mice at day 60. In parallel, cultured murine olfactory sensory neurons (OSNs) infected with SeV or UV-SeV were tested for odorant-mixture response by measuring changes in intracellular calcium concentrations indicated by fura-4 AM assay.Mice infected with SeV suffered from olfactory dysfunction, peaking on day 15, with no loss observed with UV-SeV. At 60 days, four out of 12 mice infected with SeV still had not recovered, with continued normal function in controls. Viral copies of SeV persisted in both the olfactory epithelium (OE) and the olfactory bulb (OB) for at least 60 days. At day 10 and after, both unit length labeling index (ULLI) of apoptosis and ULLI of proliferation in the SeV group was markedly less than the UV-SeV group. In primary cultured OSNs infected by SeV, the percentage of cells responding to mixed odors was markedly lower in the SeV group compared to UV-SeV (P = 0.007).We demonstrate that SeV impairs olfaction, persists in OE and OB tissue, reduces their regenerative ability, and impairs the normal physiological function of OSNs without gross cytopathology. This mouse model shares key features of human post-viral olfactory loss, supporting its future use in studies of PVOD. Further testing and development of this model should allow us to clarify the pathophysiology of PVOD.